PENGARUH METODE LATIHAN DRILL TERHADAP KEMAMPUAN SHOOTING PESERTA EKSTRAKURIKULER FUTSAL SMK PANCA KARSA SUNGAI PINYUH - Syech Zainudin; Andika Triansyah; Fitria Puspa Hidasari (Universitas Tanjungpura, 2021)
AbstractThis study aims to determine the effect of the drill training method on the shootingability of futsal extracurricular participants at Panca Karsa Sungai Pinyuh VocationalSchool. This study uses an experimental method with the design of